Occurrence of dental caries in people with attention deficit hyperactivity disorder (ADHD) – literature review - Mielnik-Błaszczak, Maria; MAŚLANKO, MONIKA; Błaszczak, Jerzy; SKAWIŃSKA- BEDNARCZYK, AGNIESZKA; PIETRAK, JUSTYNA (Journal of Stomatology, 2017)
Attention deficit hyperactivity disorder (ADHD) is one of the most common neurobehavioral disorders in children and adolescents. An estimated 3-5% of children in the developmental age are affected. ADHD is associated with an increased risk of other mental disorders, obesity, propensity for addiction, and the development of diseases of the oral cavity. This paper attempts to summarize the existing research on the impact of ADHD on the occurrence of dental caries. Previous studies have shown that children and adolescents with ADHD are at a higher risk; however, the reasons for this association are not fully understood. It appears that the pharmacological treatment does not play a significant role since the resulting decrease of saliva secretion is negligible. It is believed, however, that nutritional and hygienic habits have a large effect, contingent upon specific character traits of people with the discussed disorder. The results of the previous studies are inconclusive and the subject requires further study and analysis. The aim of this paper is to summarize current knowledge on the prevalence of dental caries in children and adolescents with ADHD. This analysis is also meant to help determine the reasons as to why a person with diagnosed ADHD is at an increased risk of dental caries.